The Development and Application of Rubrics in Education: A Scopus-Based Systematic Literature Review (2016–2026) - Ahmad Hanafi Nurmawansyah; Aji Joko Budi Pramono (Pedagogi : Jurnal Pendidikan dan Pembelajaran, 2026)
Rubric is an assessment instrument that plays a central role in supporting transparency and consistency of evaluation in education. This study aims to map the development, application, and effectiveness of rubrics in education through the Systematic Literature Review (SLR) approach following PRISMA 2020 guidelines. A literature search was conducted using keywords ("rubric" AND "education") in the Scopus database selected for its broad coverage of high-quality international journals and its concentration of Q1 and Q2 publications in education yielding 186 initial records. After selection stages based on the 2016–2026 range, Q1–Q4 journal rankings, abstract availability, and full-text feasibility screening using the Watase Uake automated SLR tool, a total of 13 articles were selected as the corpus of analysis. Given the single-database approach, these findings should be understood as representative of high-impact Scopus-indexed literature rather than an exhaustive mapping of the entire rubric research field. The results show that the development and use of rubrics in education has increased significantly in the last decade, with diverse focuses including: (1) competency-based formative assessment; (2) self-assessment and self-directed learning; (3) integration of artificial intelligence in automated assessment; and (4) cross-disciplinary competency development covering the fields of STEAM, bioinformatics, and language education. Methodologically, the research analyzed was dominated by qualitative approaches and instrument development, followed by quantitative and mixed methods, with most research conducted in higher education contexts. These findings imply the need for more systematic standardization in rubric development, strengthening educators' capacity to use rubrics as learning tools, and further exploration of the role of technology in educational evaluation.